2016
DOI: 10.9734/bmrj/2016/23391
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Microbial Contamination of Processed Beef Meat by Using API Strips and Automated Vitek 2 Compact System

Abstract: This work was carried out in collaboration between both authors. Author YAS designed the study, performed the statistical analysis, wrote the protocol, managed the analyses of the study, literature searches and supervised the laboratory work. Author AAA wrote the first draft of the manuscript, managed literature searches and carried the laboratory work. Both authors read and approved the final manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Another hypothesis could be a failure in identification when using the API ® 20E test. In fact, Ahmed and Sabiel also used this commercial kit to identify their isolates [21]. According to the results provided by the API ® 20E kit, in six of the ten isolates of this microorganism in this study, the probability percentage (ID %) was equal to or greater than 84.6%, reaching up to 98.5%.…”
Section: Unusual Identification Of Mannheimia Haemolyticamentioning
confidence: 69%
See 2 more Smart Citations
“…Another hypothesis could be a failure in identification when using the API ® 20E test. In fact, Ahmed and Sabiel also used this commercial kit to identify their isolates [21]. According to the results provided by the API ® 20E kit, in six of the ten isolates of this microorganism in this study, the probability percentage (ID %) was equal to or greater than 84.6%, reaching up to 98.5%.…”
Section: Unusual Identification Of Mannheimia Haemolyticamentioning
confidence: 69%
“…This bacterium occasionally intervenes in the porcine respiratory complex, although it is much more frequent in bovines where it also causes respiratory disease. Ahmed and Sabiel also identified M. haemolytica in minced beef [21].…”
Section: Unusual Identification Of Mannheimia Haemolyticamentioning
confidence: 94%
See 1 more Smart Citation
“…were found to be among the predominant bacteria in lamb meat (Wang et al, 2019). According to Ahmed and Sabiel (2016), the members of the family Enterobacteriaceae are usually associated with the contamination of meat products, their incidence in meat was considered as a public health problem. It was found that S. aureus was the most frequent bacterium present in fresh lamb meat.…”
Section: Discussionmentioning
confidence: 99%